Numerical Study of Experiment Setup for Aluminum Foam Sandwich Construction Subjected to Blast Load - Arief Nur Pratomo; Sigit Puji Santosa; Leonardo Gunawan; Ichsan Setya Putra (Mesin, 2018)
In the designing an armored fighting vehicle (AFV), blastworthy construction to protect military personnel from landmines explosion is urgently needed. This is due to a large number of fatalities of army personnel in the state conflict zones. To achieve this blastworthy construction, the design of AFV floor structures needs to be able to sustain structural intrusion with lower dynamic acceleration against blast load. The blastworthy structures can be achieved through absorbing the blast impact load by using an aluminum foam sandwich (AFS) construction. During the design iteration process, a good correlation between numerical simulation and blast impact experiment is required. In this study, an experimental setup to assess the AFS construction for blast load performance evaluation was introduced. This study is started with an evaluation of jigs and fixtures structural strength, load cell structure requirement, and data acquisition to record maximum displacement, maximum acceleration, and reaction force in the load cells. From the evaluation, it was found that the jig and fixture structural configuration requires high load retention at the bolt joint location to avoid high stress concentration. For the load cell structure, it is recommended to place the load cell position in the pure axial stress direction so that there is no plastic deformation interference with the instrumentation. The data acquisitions will record the acceleration and reaction force of the AFS construction. The simulation results are also used to design the load cell and to select the accelerometer capability range. This study is expected to provide a robust experimental data during blast impact load testing of blastworthy AFS floor structure.